A Web-Based Dementia Education Program and its Application to an Australian Web-Based Dementia Care Competency and Training Network: Integrative Systematic Review - Moehead, Anne; DeSouza, Kathryn; Walsh, Karen; Pit, Sabrina W (JMIR Publications, 2020)
BackgroundDementia education that meets quality and safety standards is paramount to ensure a highly skilled dementia care workforce. Web-based education provides a flexible and cost-effective medium. To be successful, Web-based education must contain features that promote learning and support knowledge translation into practice. The Dementia Care Competency and Training Network (DCC&TN) has developed an innovative Web-based program that promotes improvement of the attitudes, knowledge, skills, behavior, and practice of clinicians, regardless of their work setting, in order to improve the quality of life for people living with dementia. ObjectiveThis review aims to (1) determine the key features that are associated with an effective and functional Web-based education program-an effective and functional Web-based program is defined as one that measures results, is accessible, is user friendly, and translates into clinical practice-and (2) determine how these features correlate with the DCC&TN. MethodsSix electronic databases-Medline, Embase, Cumulative Index to Nursing and Allied Health Literature (CINAHL), AusHealth, Nursing@Ovid, and Google Scholar-were searched for articles published between 2009 and 2018 using the following keywords: Education, Distance, Continuing, Learning, Online, Web-Based, Internet, Dementia, Program Evaluation, Validation Studies, Outcome and Process Assessment Healthcare, Nursing, Assisted Instruction, and Facilitated. The Critical Appraisal Skills Programme (CASP) and Kirkpatrick's model for the evaluation of training were used to ensure quality and rigor of the analysis. ResultsA total of 46 studies met the inclusion criteria. In total, 14 key features were associated with an effective Web-based learning environment, which enabled the environment to be as follows: self-directed, individualized, interactive, multimodal, flexible, accessible, consistent, cost-effective, measurable with respect to participant satisfaction, equitable, facilitated, nurturing of critical thinking and reflection, supportive of creating a learning community, and translated into practice. These features were further categorized into five subgroups: applicability, attractiveness, functionality, learner interaction, and implementation into practice. Literature frequently cites Kirkpatrick's four-level model of evaluation and application in the review of education and training; however, few studies appeared to integrate all four levels of Kirkpatrick's model. Features were then correlated against the DCC&TN, with an encouraging connection found between these features and their inclusion within the content and structure of the DCC&TN. ConclusionsA total of 14 key features were identified that support an effective and functional Web-based learning environment. Few studies incorporated Kirkpatrick's salient elements of the model-reaction, learning, behavior, and results-in their evaluation and clinical application. It could, therefore, be considered prudent to include Kirkpatrick's levels of training evaluation within studies of dementia training. There were few studies that evaluated Web-based dementia education programs, with even fewer reporting evidence that Web-based training could increase staff confidence, knowledge, skills, and attitudes toward people with dementia and be sustainable over time. The DCC&TN appeared to contain the majority of key features and is one of the few programs inclusive of hospital, community, and residential care settings. The 14 key features can potentially enhance and complement future development of online training programs for health sciences education and beyond. The DCC&TN model could potentially be used as a template for future developers and evaluators of Web-based dementia training.